Singleton-Merten syndrome: a rare cause of femoral head necrosis - Assaf, Elio; Bdeir, Mohamad; Mohs, Elisabeth; Dally, Franz; Gravius, Sascha; Weis, Cleo-Aron Thias; Darwich, Ali (American journal of medical genetics, 2021)
Singleton-Merten syndrome (SMS) is a type I interferonopathy. In this report, we disclose the first—to the best of our knowledge—direct association of SMS with femoral head necrosis (FHN). The following case report presents the condition of a 38-year-old male suffering from SMS with FHN, characterized by acute symptoms and rapid disease progression. As per the recommendations of the Association Research Circulation Osseous (ARCO) and the S3-guidelines, we successfully treated the FHN with core decompression. Our histological results correlate with the changes described in medical literature in patients with SMS and MDA5-knockout in vivo experiments such as osteopenia, widened medullary cavity, and thin cortical bone. Moreover, the conducted immunohistochemistry shows strong CD56 positivity of the osteoblasts and osteocytes, as well as significant CD68 and CD163 positivity of the middle-sized osteoclasts. Collectively, these findings suggest an underlying syndrome in the FHN. A six-month post-operative follow-up revealed complete recovery with the absence of the initial symptoms and ability to resume normal daily activities. Taken together, our findings suggest that SMS is an additional cause of FHN in young adults. Early detection and adequate treatment using well-established joint-preserving techniques demonstrate a favorable improvement of the patient's clinical condition.